Self-Determination Theory Applied to Health Contexts: A Meta-Analysis - Ng, J.; Ntoumanis, Nikos; Thøgersen-Ntoumani, Cecilie; Deci, E.; Ryan, R.; Duda, J.; Williams, G. (Sage Publications, Inc., 2012)
Behavior change is more effective and lasting when patients are autonomously motivated. To examine this idea, we identified 184 independent data sets from studies that utilized self-determination theory (SDT; Deci & Ryan, 2000) in health care and health promotion contexts. A meta-analysis evaluated relations between the SDT-based constructs of practitioner support for patient autonomy and patients’ experience of psychological need satisfaction, as well as relations between these SDT constructs and indices of mental and physical health. Results showed the expected relations among the SDT variables, as well as positive relations of psychological need satisfaction and autonomous motivation to beneficial health outcomes. Several variables (e.g., participants’ age, study design) were tested as potential moderators when effect sizes were heterogeneous. Finally, we used path analyses of the meta-analyzed correlations to test the interrelations among the SDT variables. Results suggested that SDT is a viable conceptual framework to study antecedents and outcomes of motivation for health-related behaviors.